2020
DOI: 10.20867/thm.26.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivation, Satisfaction and Revisit Intention of Ecolodge Visitors

Abstract: Purpose – This paper demonstrates that the recommendations regarding visitor satisfaction and revisit intention reported in the international literature apply to the management of ecolodges in Sri Lanka. Design/Methodology/Approach – Data from 362 self-report questionnaires completed by visitors between January 2014 and January 2015 were analysed by structural modelling using SPSS and AMOS to confirm the significance that reported direct and indirect relationships of the latent factors ecolodge attributes, tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
11
0
4
Order By: Relevance
“…In the context of tourism, service quality, satisfaction, involvement, previous experience, place attachment, and perceived value can influence guests' intentions to revisit [128][129][130]. Of these, satisfaction is one of the most important determinants, which is widely understood in tourism experiences [56,131]. Several studies have proven that the more the guests express their satisfaction with destinations, the more likely they will be to revisit [132,133].…”
Section: Revisit Intentionmentioning
confidence: 99%
“…In the context of tourism, service quality, satisfaction, involvement, previous experience, place attachment, and perceived value can influence guests' intentions to revisit [128][129][130]. Of these, satisfaction is one of the most important determinants, which is widely understood in tourism experiences [56,131]. Several studies have proven that the more the guests express their satisfaction with destinations, the more likely they will be to revisit [132,133].…”
Section: Revisit Intentionmentioning
confidence: 99%
“…Simpson et al, [88] Identifying factors influencing revisit intention of ecolodge visitors 362 visitors to Sri Lankan ecolodges…”
Section: Chi-square or T Testsmentioning
confidence: 99%
“…unsustainable ecotourism business practices [23,76,77], 2) profile of ecotourists, their motivations, characteristics, attitudes, satisfaction and related segmentation [39,[78][79][80][81][82][83][84][85][86][87][88][89][90], 3) service quality, attributes, performance goals and sustainable management of ecolodges [15,18,[91][92][93][94]] 4) contribution of ecolodges in local sustainable development [95][96][97], and 5) miscellaneous themes namely private tourism ecolodge concessions, pedagogical process for designing an ecolodge [98,99].…”
Section: Institutional Review Board Statement: Not Applicablementioning
confidence: 99%
“…With the rising demand for natural area tourism in Sri Lanka, the demand for alternative accommodation choices has also increased ( Sumanapala et al . 2015 , 2017 ; Simpson et al . 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the variability in environmental conditions, the magnitude and level of use, site specific physical developments at campsites, and campsite visitor characteristics (such as visitor behaviours, attitude, and environmental orientation) such research findings may have some limited applicability in the Tropical Asian context. Furthermore, several authors have reported on the importance of demonstrating the local relevance of research and management practices in order to sustain or enhance nature-based tourism experiences ( Bandara 2009 ; Fernando & Kaluarachchi 2016 ; Simpson et al . 2020 ; Marasinghe et al .…”
Section: Introductionmentioning
confidence: 99%